Kepatuhan Hukum Pengusaha Dalam Menunaikan Zakat Perikanan - Faradika, Faradika; Analiansyah, Analiansyah; Desiana, Rina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Fisheries zakat is zakat imposed on the results of the fishery business, both obtained through cultivation and fishing, and paid at harvest time. This zakat must be paid if the harvest reaches nisab equivalent to 85 grams of gold. Most of the medium-to-upper scale fishery entrepreneurs have the potential to achieve nisab zakat. However, there are still fishery entrepreneurs who do not pay zakat. This study aims to analyze the ability of fishery entrepreneurs in Banda Aceh City to pay zakat based on income from fish catches. And analyze aspects of fulfilling indicators of legal compliance of fisheries entrepreneurs in paying zakat. This research is an empirical legal research using a qualitative approach. The research data was analyzed by descriptive-analysis method. The results of the study show that fishery entrepreneurs in the city of Banda Aceh have fulfilled the nisab of income zakat. Indicators of legal compliance in paying zakat fulfilled by fishery entrepreneurs are indicators of trust and acceptance. Where fish entrepreneurs believe and accept the existence of zakat obligations. In general, fisheries entrepreneurs in Banda Aceh City are categorized as non-compliant with the law in fulfilling their zakat obligations. The contribution of this research is that it can be a reference for the formulation of strategic policies in increasing zakat compliance through more effective educational, regulatory, and institutional approaches.